A Study on Spiramycine in Acute Tonsillitis and Sinusitis - Ullah, Mohib (Journal of Postgraduate Medical Institute, 2011)
the objective of the study was to assess the efficacy and tolerance of Rovamycine forte (spramycine) in cases of acute Tonsillitis and sinusitis. It was a prospective non comparative, open ended, cliical trial, in 60 patients, at the out patient department of LRH, Peshawar. it was conducted during November 1994 to march 1995. The results showed overall efficacy of the drug to be 90% and excellent to good tolerance as 91%, for both indications. Thus, rovamycine Forte (Spiramycine) proved to be an excellent macrolide, to be recommended in common upper Respiratory tract Infections (URTI) e.g. Acute Tonsillitis and sinusitis. its short therapy, has an added advantage in terms of compliance.